Спасенный день: стихи / А. Белоногов, перевод с удмуртского - Белоногов Александр Егорович (Удмуртия, 1987)
Экземпляры: ф.1 (20190910) / Инвентарный номер: 15939 / Цена: 0.25 / Авт.знак: Б-43 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5